Advance Organizer Model-Based Teaching Materials for Islamic Cultural History - Amin, Alfauzan; Alimni, Alimni (Journal of Education Technology, 2022)
The obstacles that are often faced in learning Indonesian history are the lack of facilities and infrastructure, especially in terms of electronic media. This study aims to develop teaching materials based on the advance organizer model in the subject of Islamic cultural history. This research is a type of development research. The sample in this study used cluster sampling consisting of small group tests and large group tests. The sample in this study used a cluster sampling technique. Cluster sampling is a sampling technique through the formation of units. The sample in this study consisted of a small group test and a large group test. The small group test was conducted as many as 20 students of class V were selected from rank 1 to 10 from the top (4 boys, 6 girls) and the last 10 students ranked (5 boys, 5 girls) from class V. For large group trials with a total of 109 students (class A and class B). The instrument in this study is in the form of response and perception. The data analysis technique in this study used descriptive and infetetial (T-test). The results of the T test for the experimental class and control class using SPSS 20 having difference. This means that there is a significant difference between the average score of student learning outcomes at experimental class and control class where the two schools apply the advanced organizer learning model.